Video-assisted ovariohysterectomy in domestic cats (Felis catus, linnaeus, 1758) using two access portals - Tavares, Denise Cláudia [UNESP]; de Souza, Fabiana Ferreira; Quarterone, Carolina; Rodrigues, Valeska; Pereira, Lucas de Freitas; Brun, Maurício Veloso; Toniollo, Gilson Hélio [UNESP] (FapUNIFESP (SciELO), 2016)
PURPOSE: To describe video-assisted ovariohysterectomy (OHE) with two portals access in adult intact queens. METHODS: Fifty-two females cats were used. A 4 mm cannula was positioned in the abdomen through an incision close to the umbilicus (first portal), and a pneumoperitoneum was established. A second portal was positioned in the midline of the pre-pubic region. Females were positioned in right lateral recumbency to locate the left ovarian pedicle, and the uterine horn was held by a transcutaneous suture. The pedicle was cauterized and incised. The procedure was then performed on the contralateral ovary. The ovaries were exteriorized from the abdomen, along with the uterus, through the second access point. The uterine body was exposed, fixed and sectioned, and the abdominal incisions were sutured. RESULTS: Surgeries were performed in an average of 41.4±14.2 minutes. The main complications included hypotension (7.7%) and subcutaneous emphysema (7.7%), and 13.5% of the surgeries were converted to laparotomy. CONCLUSION: Ovariohysterectomy using a video-assisted technique and two access portals is safe, has minimal risks and is effective for the spaying of queens.
Keywords: Castration; Cats; Hysterectomy; Ovary; Video-assisted surgery